Soil respiration in the vicinity of Syowa Station, Antarctica 2. Estimation of carbon dioxide amount evolved from the naked part of West Ongul Island - Yoshio Ino; Yasuyuki Oshima; Yoshikuni Ohyama; Hiroshi Kanda; Tatsuro Matsuda (National Institute of Polar Research, 1981)
In January and February 1979,48 samples of surface sandy soil were taken at East and West Ongul Islands. The soil respiration rates, i. e. carbon dioxide evolution rates, of the samples were measured with the infrared gas analyzer. There were positive correlations between the soil respiration rate and the water content, the nitrogen content or the organic carbon content. Meshes of 5mm×5mm squares were laid on the contour map of West Ongul Island on the scale of 1 : 5000. The soil respiration rate in each mesh was estimated from the geographical features. The carbon dioxide evolution amount in West Ongul Island was calculated at 2.1t CO_2-C during a period from December to February. This amount corresponds to 7.7kg C/ha of the ice-free area without the moss community.